China and Japan’s strategic competition in east Asia: The case of the east China sea - Tuan, Nguyen Khoa; Le, Vu Thi Phuong (Edelweiss Applied Science and Technology, 2025)
The East China Sea is an area of strategic significance in Sino-Japanese relations and security in the Asia-Pacific region. This article analyzes the strategic competition between China and Japan in the East China Sea during the period of 1991-2024, focusing on the Senkaku/Diaoyu Islands dispute and maritime security issues. The study uses historical-logical, analytical and synthetic, and comparative methods, based on official sources and research works by international scholars to clarify the current situation of competition between the two Asian powers. The content is implemented in two main directions: analyzing the developments and nature of Sino-Japanese competition in the East China Sea, and assessing its prospects and impacts on the regional security situation. The research results not only clarify the dynamics and characteristics of strategic competition but also provide a scientific basis for forecasting the trend of bilateral relations and the situation in the East China Sea in the context of many fluctuations in the regional order.